Pengaruh Structural Assurance dan Situational Normality terhadap Trust Bertransaksi di Sistem E-Commerce - Dharma, Fitra (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2006)
The research aims to reveal an empirical evidence whether structural assurance belief and situational normality belief have positive effect to trust in e-commerce system. Data for the study are collected from 100 Internet's user. It used multiple regression to analyze the data. The results indicate that perception of structural assurance has significant effect on trust in e-commerce site. However we failed to find out empirical evidence that situational normality belief has significant effect either.